EFFECTIVENESS OF ALTERNATIVE PRODUCTS AGAINST APPLE PESTS [ÚČINNOST ALTERNATIVNÍCH PŘÍPRAVKŮ PROTI ŠKŮDCŮM JABLONÍ] - Michal Skalský; Jana Ouředníčková (Vědecké Práce Ovocnářské)
In recent years, there has been a significant restriction on the spectrum of active substances that can be used in fruit growing in the Czech Republic. This fact creates challenges in implementing effective protection systems against many pests. The limitation of active substances and the absence of effective replacements are also related to the selection of resistance to pesticides in certain species, the accumulation of specific residues of active substances in the environment, negative impacts on non-target organisms, etc. The presented study focuses on the issue of alternative products and plant protection aids that could have potential use in protecting against harmful organisms and could thus replace classical insecticidal active substances at certain stages of vegetation. In laboratory or operational trials, the effectiveness of selected natural-based products, mostly oils, was evaluated against the woolly apple aphid and European red mite. According to the results obtained, high effectiveness was achieved against the blood aphid with the products Rock Effect NEW and Neudosan. The population of overwintering eggs of the fruit spider mite can be reduced in the pre-spring period with the products Rock Effect NEW and Ekol at a dose of 30 l/ha.